KONSTRUKSI GENDER DALAM NOVEL “TSUKUSHISA TO KANASHIMI TO” KARYA YASUNARI KAWABATA - Anastasia Dewi Wulandari; Aquarini Priyatna; Lina Meilinawati Rahayu (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Utsukushisa to Kanashimi to novel was written by Yasunari kawabata, published 1969. This research followed by the analysis of gender construction Otoko within patriarchy environment. Feminist literature critism is a discourse emphasizing on how literature should be done through feminist perpektive. The important things of feminist literature critism are the way the women are described, how a text could be related to gender, and any feminist ideas depicted in the story. The result of this research proves that Otoko faces gender construction such as marginalization, subordinations, sterotyping and sexual violences. Meanwhile, the ideas of feminism in the story are about a woman‟s independence.